Re-evaluation of the taxonomic status of Vegaranina (Crustacea: Raninidae) from the Late Cretaceous of Cuba, with description of a new species - Arano-Ruiz, Alberto; Viñola-López, Lazaro W.; Rojas-Consuegra, Reinaldo; Borges-Sellen, Carlos Rafael (Zootaxa, 2018)
A new species of raninid crustacean, Vegaranina rivasi sp. nov, is described based on three specimens collected from a Late Cretaceous deposit in central Cuba. Previous studies assigned one of the specimens to Vegaranina precocia (Feldmann, Vega, Tucker, Garcia-Barrera & Avendano, 1996), a species described from the Late Cretaceous of Mexico. However, after collecting the new specimens and recent major revisions of the group, we identified a unique combination of characters in the Cuban specimens that separate them from the other species in the genus.